Students' Perception of Oral Presentation Assignment Using PowerPoint in English Education Students - Deva Rizkiatun Naelufah; Fadiah Nuriman Dalika; Intan Hazawa; Siti Zulfa (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2023)
In the English classroom, students are assigned to conduct oral presentations using PowerPoint as one of the visual aids. The study aimed to investigate the perceptions of English education students about oral presentations and classroom assignments using PowerPoint. The researchers employed qualitative methods and purposively selected a sample of 30 college students in the 5th semester of English education at one of the higher education institutions in Indonesia. The research instruments were Likert scale questionnaires and interviews. The data analysis used a thematic analysis. The result indicated that most students' perceptions were positive towards oral presentations using PowerPoint, which served as an assignment. Also, it highlights that oral presentations can enhance students' understanding and retention if the slides contain only important points, interesting pictures, or animation rather than full text. This research pointed out that students thought oral PowerPoint presentations were inefficient due to external factors such as a lack of internet connection and device preparation. Therefore, the oral presentation assignments using PowerPoint become necessary by considering the learning activity to obtain the learning objectives.